Phase-separated vortex-lattice in a rotating binary Bose–Einstein condensate - Adhikari, S. K. [UNESP] (Elsevier, 2019)
We study circularly-symmetric phase separation of vortex lattices in a rapidly rotating harmonically-trapped quasi-two-dimensional binary Bose–Einstein condensate (BEC) by introducing a weak quartic trap in one of the components. The increase of the rotational frequency in such a system is also found to generate a phase separation of the vortex lattices of an overlapping non-rotating BEC. The phase-separated vortex lattices have different structures for a binary BEC with inter-species repulsion and inter-species attraction. In the former case of a fully repulsive binary BEC, the phase separation of the vortex-lattices is accompanied by a complete phase separation of component densities. In the latter case of inter-species attraction, there is a partial phase separation of component densities, although there could be a complete phase separation of the generated vortex lattices in the two components. In the case of inter-species attraction, we need to have different intra-species repulsion in the two components for an efficient phase separation. We compare and contrast our results with the phase separation obtained in a harmonically-trapped binary BEC without any quartic trap.
Keywords: Gross–Pitaevskii equation; Rotating Bose–Einstein condensate; Split-step Crank–Nicolson scheme; Vortex lattice